Artemisinin-Loaded Nanofibrous Scaffolds: A Potential Strategy for Enhancing Apoptosis and Inhibiting Breast Cancer Survival - Akram Firouzi Amandi; Sodabeh Aminitekantapeh; Mehdi Dadashpour (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Breast cancer remains one of the most prevalent cancers affecting women worldwide. Despite advances in conventional treatments such as chemotherapy, surgery, hormone therapy, and radiotherapy, their effectiveness in eradiating the disease is often limited. This study was conducted to explore the anticancer potential of artemisinin-based electrospun implantable scaffolds against the MDA-MB231 breast cancer cell line. Materials and methods: Artemisinin (Art)-loaded polycaprolactone scaffolds (Art-PCL NFs) were synthesized using electrospinning technique and their physical and chemical properties were characterized through electron microscopy and infrared spectroscopy. This experimental study involved the preparation and culture of MDA-MB231 cells in triplicate wells for both test and control groups. In the test groups, five concentrations of artemisinin in its free and nanoformulated form (0, 2, 5, 10, 20, and 30 mM) were applied and incubated for 24, 48, and 72 hours. The control group was incubated with cell culture medium without any treatment. The MTT assay was conducted to evaluate the cytotoxic effects of nanofibers containing Art on the MDA-MB231 cell line. Additionally, the expression levels of BCL2 and Bax genes in breast cancer cells treated with Art-PCL NFs were analyzed using Real-Time PCR. Data were analyzed using an unpaired t-test and GraphPad Prism version 8, and Excel software. Results: The MTT assay demonstrated that loading artemisinin onto polycaprolactone scaffolds significantly enhanced its cytotoxic effect on MDA-MB231 cancer cells (P<0.05). This effect was associated with a significant increase in the expression level of Bax gene and a corresponding decrease in BCL2 expression in cells treated with Art-PCL NFs compared to those with pure Art (P<0.05). Conclusion: The study showed that Art-PCL NFs are more effective in increasing the expression of genes associated with apoptosis and inhibiting anti-apoptotic genes compared to pure Art. Therefore, nanofiber-based Art-PCL NFs could serve as potential drug delivery system for targeting the residual cancer cells and preventing breast cancer recurrence.